Isolated tubal ischemia secondary to small bowel volvulus: a rare case report - Boukroute, Marouane; Regragui, Abdelmajide; Chatbi, Zaineb; Bellajdel, Ibtissam; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Torsion of the fallopian tube is a rare cause of acute abdominal pain, often underrecognized in the context of intestinal pathology. We reported the case of a 30-year-old woman who developed isolated fallopian tube ischemia secondary to small bowel volvulus, a complication rarely described. She presented with acute hypogastric pain, vomiting, and mild left hydronephrosis. CT imaging revealed a small bowel obstruction with a whirlpool sign but no apparent tubal abnormalities. Laparotomy identified a twisted, ischemic fallopian tube with hydrosalpinx, attributed to adhesions from a recent appendectomy. Salpingectomy, small bowel resection, and anastomosis were performed, with histopathology confirming ischemic necrosis. This case underscores the diagnostic challenge posed by overlapping gastrointestinal and gynecological emergencies and suggests that vascular compromise in small bowel volvulus may extend to pelvic structures. Given the rarity of secondary tubal torsion, clinicians should consider this possibility in women with prior pelvic surgery and acute abdominal pain. Early CT imaging and interdisciplinary collaboration are essential for timely intervention and improved outcomes.